Menopausal Symptoms among Postmenopausal Women of a Selected Municipality: A Cross-sectional Survey - Sitasma Sharma (Nepal Medical Association, 2021)
Introduction: Postmenopausal women experience various menopause-specific somatic, psychological, and urogenital symptoms which tend to affect their overall well-being. However, there is a scant focus on menopausal health problems of postmenopausal women in Nepal. The aim of the study was to find out the prevalence of menopausal symptoms among postmenopausal women of a Municipality.